Language Acquisition and Teaching Strategies for Children with Mental Retardation - Satria, Dadi; Widodo, Pratomo (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2023)
Delays in language acquisition and learning experienced by children with mental retardation cause the language production process to be disrupted. This study aims to describe and find the right strategy for language teaching in children with mental retardation aged 5;0 – 10;0 years. This study is a qualitative study using a descriptive method. The research findings show that: (1) the word classes mastered by children with mild mental retardation include nouns, verbs, numerals, adjectives, interrogatives, and prepositions. (2) The types of meanings mastered include referential meaning and denotative meaning, (3) The research subjects are also at the meaning field stage, meaning that children have been able to classify words based on their respective meaning fields. (4) Cooperative learning strategies are considered more effective for teaching language to mentally retarded children. This research is expected to contribute to efforts to acquire and teach language to mentally retarded children aged 5;0 – 10;0 years.